Review of the family Coccidae (Hemiptera: Coccomorpha) in Laos - Choi, Jinyeong; Soysouvanh, Pheophanh; Lee, Seunghwan; Hong, Ki-Jeong (Zootaxa, 2018)
The family Coccidae Fallén, 1814 (Hemiptera: Coccomorpha), known as soft scale insects, is represented in Laos by 26 species. This includes 15 new country records: Ceroplastes cirripediformis (Comstock, 1881), C. floridensis Comstock, 1881, Coccus capparidis (Green, 1904), C. celatus De Lotto, 1960, C. formicarii (Green, 1896), C. gymnospori (Green, 1908), C. latioperculatum (Green, 1922), Drepanococcus cajani (Maskell, 1891), Eucalymnatus tessellatus (Signoret, 1873), Megapulvinaria maxima (Green, 1904), Paralecanium expansum (Green, 1896), Pulvinaria floccifera (Westwood, 1870), P. psidii Maskell, 1893, Saissetia miranda (Cockerell & Parrott in Cockerell, 1899), and S. oleae (Olivier, 1791). An identification key to adult females of all the soft scale species known from Laos is provided, together with diagnoses, photographs and host information. The economic importance of each species is also discussed.